Expression of HOXC8 is inversely related to the progression and metastasis of pancreatic ductal adenocarcinoma - Adwan, Hassan; Zhivkova-Galunska, M.; Georges, R.; Eyol, E.; Kleeff, J.; Giese, Nathalia; Friess, H.; Bergmann, Frank; Berger, M. R. (British journal of cancer, 2011)
Background: The transcription factor HOXC8 regulates many genes involved in tumour progression. This study was to investigate the role of HOXC8 in pancreatic ductal adenocarcinoma (PDAC) growth and metastasis. Methods: The Hoxc8 expression was determined in 15 PDAC cell lines and human specimens by RT–polymerase chain reaction and/or immunohistochemistry. The effects of HOXC8 silencing by RNA interference were investigated by functional tests. Results: The Hoxc8 mRNA expression in PDAC cell lines was negatively related to their growth in vivo. Except for Suit2-007 cells, only those with low Hoxc8 mRNA expression grew in nude rats. Successful down-regulation of HOXC8 expression caused increased proliferation, migration (P⩽0.05) and colony formation (P⩽0.05) in Suit2-007, Panc-1 and MIA PaCa-2 PDAC cells, respectively. The Hoxc8 mRNA levels in diseased human pancreas tissues were significantly increased over normal in PDAC and autoimmune chronic pancreatitis specimens (P<0.01, respectively), but negatively related to tumour stage (P=0.09). In primary and metastatic tumour samples, immunohistochemical staining for HOXC8 was stronger in surrounding than in neoplastic tissues. Furthermore, grading of primary carcinomas was negatively associated with HOXC8 staining (P=0.03). Liver metastases showed the lowest HOXC8 expression of all neoplastic lesions. Conclusion: These data indicate that HOXC8 expression is inversely related to PDAC progression and metastasis.
Gesehen am 28.02.2022